Negotiating the Traffic: Can Cognitive Science Help Make Autonomous Vehicles a Reality?. Issue 2 (February 2018) - Chater, Nick; Misyak, Jennifer; Watson, Derrick; Griffiths, Nathan; Mouzakitis, Alex
Abstract : To drive safely among human drivers, cyclists and pedestrians, autonomous vehicles will need to mimic, or ideally improve upon, humanlike driving. Yet, driving presents us with difficult problems of joint action: 'negotiating' with other users over shared road space. We argue that autonomous driving provides a test case for computational theories of social interaction, with fundamental implications for the development of autonomous vehicles.